Phenomenal AOC : the roots and rise of Alexandria Ocasio-Cortez - Denise, Anika (Harper, an imprint of HarperCollins Publishers, 2022)
An inspiring biography of Congresswoman Alexandria Ocasio-Cortez from Pura Belpré Honor-winning creators Anika Aldamuy Denise and Loris Lora! In 2019, Alexandria Ocasio-Cortez became the youngest congresswoman in America. How did this young Puertoriquena become an unstoppable force in politics? Find out in this accessible and engaging book for young readers. AOC's remarkable story begins in her childhood Bronx home and comes full circle the moment AOC became America's youngest Congresswoman. Ocasio-Cortez's empowering journey reminds us that everyone, regardless of their age, race, creed, wealth, or zip code, is capable of being a voice for change. A glossary and resources for changemakers are included at the end of the book.